STUDI PERAN MANAJERIAL PENGURUS CABANG ORGANISASI IKATAN BIDAN INDONESIA DALAM PELAYANAN ANTENATAL CARE OLEH BIDAN PRAKTEK MANDIRI DIKOTA SEMARANG - Hanif, Azizah (Jurnal Kesehatan Masyarakat (Undip), 2015)
Antenatal service has significant role in preventing the decreasing trend of AKI and AKB. This service is on the right momentum to detect any abnormality or disease within mother and fetus in early stage. Indonesian Midwives Association as professional organization gives antenatal service which is held regularly by its committees and members. Indonesian Midwives Association’s organizing committee in Semarang has organized several seminars and trainings regarding quality of antenatal services for its members. In other hand, independently practiced midwives has not given the best practice in doing so. Based on that problem, this research was conducted to explain caretaker managerial role study of Indonesian Midwives Association’s organizing committee regarding Antenatal Service in Semarang. This research uses qualitative study that aiming to describe managerial role as leader and source of information. Informant in this research were organizing committee of Indonesian Midwives Association in Semarang area. The result showed that role of Indonesian Midwives Association’s organizing committee, as the leader in conducting antenatal service particularly in motivating events was by reminding the members to implement antenatal service in each meeting; evaluations were there but not being executed in exact schedule; coaching for members was implemented through meeting and there was no any awards yet to members who had conducted antenatal service. Role of committee as source of information management branch carried out through cooperation was  applied by having seminars, and refreshing events. Based on these results, it was suggested that Indonesian Midwives Association’s committee are to explain and perform socialization, arrange evaluation schedule properly and task achievement indicator target commitments and give reward for members in order to motivate them in giving better quality on antenatal service.